ESSENTIALS of Supply Chain Management - Hugos, Michael H. (Essentials series, 2024)
This practical guide describes how the supply chain operates and discusses the issues and techniques that are relevant for companies seeking to improve the management of their supply chains. This easy-to-use guide contains tips and techniques for maximizing supply chain innovation strategies, as well as real-world examples. This new edition will: Include new and updated Executive Insights Discuss the updated SCOR model (Supply-chain operations reference model is a process reference model developed and endorsed by the Supply-Chain Council as the cross-industry, standard diagnostic tool for supply chain management) Add new chapter on Supply Chain Resilience and Risk Management Completely update Chapter 10 and renamed to "The Promise of Real-Time and Sustainable Supply Chains.